Analysis of the Implementation of Sub-district Financial Management Based on Ministry of Home Affairs Regulation No. 20 of 2018 in Trimulyo Sub-district - Nur Hening, Zirly Istiya; Nuryana, Nisrina Putri; Puspaningtyas, Caecilia; Nur Salim, Al-Faris Ivan (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Sub-district financial management plays a crucial role in supporting sub-district development, but various challenges remain in its implementation, including potential irregularities and non-compliance with regulations. This study aims to analyze the implementation and level of compliance with the sub-district financial management cycle, as outlined in the Ministry of Home Affairs Regulation No. 20 of 2018, in Trimulyo Sub-district. The method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results of the study indicate that, in general, sub-district financial management in Trimulyo Sub-district has complied with the provisions at each stage, namely planning, implementation, record-keeping, reporting, and accountability, although several challenges remain, such as uncertainty regarding the timeliness of reporting, a lack of clarity in record-keeping related to the closure of the Buku Kas Umum (BKU) or general cash book, and delays in receiving budget allocation information from the central government.